The Evolving Landscape of Esophageal Cancer: A Four-Decade Analysis. Issue 9 (September 2019) - Rosemurgy, Alexander; Wilfong, Chandler; Craigg, Danielle; Co, Franka; Sucandy, Iswanto; Ross, Sharona
The incidence of esophageal cancer in the United States seems to have significantly increased since the 1970s. In undertaking this study, we sought to describe changes in the incidence, histologic type, and presenting stage of esophageal cancer over the past four decades. With Institutional Review Board approval, the Surveillance, Epidemiology, and End Results database of the National Cancer Institute was queried. Regression analysis was used to analyze data, and significance was accepted with 95 per cent probability. Forty-two thousand seven hundred thirty-nine patients had squamous cell carcinoma or adenocarcinoma located in their upper, middle, and/ or lower esophagus from 1973 through 2010, reflecting a 7.5-fold annual increase from 1973 through 2010. Squamous cell carcinoma increased annually 2.5-fold ( P < 0.001) and esophageal adenocarcinoma increased annually 57-fold from 1973 through 2010 ( P < 0.001), whereas the overall population in the United States increased only 43 per cent (215, 092, 900 to 308, 745, 538) in the same period. From 1973 through 2010, there was a significant increase in the incidence of esophageal cancer in the United States. This increase was much greater than the increase in the population in the United States. The incidence of adenocarcinoma increased much more than that of squamous cell carcinoma of the esophagus from 1973 through 2010.